2000
DOI: 10.1016/s1057-5219(00)00025-9
|View full text |Cite
|
Sign up to set email alerts
|

International acquisitions and shareholder wealth Evidence from the Netherlands

Abstract: In this article, we test wealth effects of international acquisitions using a sample of foreign acquisitions by Dutch firms during the period 1990-96. We find weak evidence that cross-border acquisitions are wealth-creating corporate activities, especially for acquisitions in the U.S. We observe further that for the West European acquisitions, benefits from internalization are larger for companies having relatively less international exposure and making acquisitions outside of their main activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 16 publications
0
27
1
2
Order By: Relevance
“…In terms of non-US countries, Kang (1993) investigates the abnormal returns of Japanese bidders in the US and finds positive abnormal returns to Japanese firms. Corhay and Rad (2000) find weak evidence that cross-border acquisitions are wealth-creating based on a sample of Dutch firms. They also find evidence that the benefits from internalisation are greater for firms having less international exposure and making acquisitions outside their main industrial activity.…”
Section: Related Literature (A) Post-acquisition Performance Of Acquimentioning
confidence: 83%
“…In terms of non-US countries, Kang (1993) investigates the abnormal returns of Japanese bidders in the US and finds positive abnormal returns to Japanese firms. Corhay and Rad (2000) find weak evidence that cross-border acquisitions are wealth-creating based on a sample of Dutch firms. They also find evidence that the benefits from internalisation are greater for firms having less international exposure and making acquisitions outside their main industrial activity.…”
Section: Related Literature (A) Post-acquisition Performance Of Acquimentioning
confidence: 83%
“…The nature of the market for corporate control in the target country can impact on acquirer's wealth (Fatemi & Furtado, 1988;Markides & Ittner, 1994;Corhay & Rad 2000). Bris & Cabolis (2008) call for further work into analysing domestic and cross border mergers, and so we add to the work of Danbolt (1995), (2004) and Danbolt & Maciver (2012), who examine returns to foreign acquirers into the UK, in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…However, their finding were inconclusive. A few studies found no significant relationship between the size and abnormal return (Bhagat et al, 2011;Cakici et al, 1996;Corhay & Rad, 2000). However, others found a positive relationship between size and cumulative abnormal return of shareholders (Basuil, 2011;Du & Boateng, 2015;Song et al, 2010a).…”
Section: Firm-specific Factorsmentioning
confidence: 99%
“…Many studies found that announcement of CBMAs created wealth for bidders (Bhagat, Malhotra, & Zhu, 2011;Cakici, Hessel, & Tandon, 1996;Chari et al, 2010;Corhay & Rad, 2000;Goergen & Renneboog, 2004;Lowinski, Schiereck, & Thomas, 2004;Martynova & Renneboog, 2008;Masulis, Wang, & Xie, 2012;Mueller & Yurtoglu, 2007;Rani, Yadav, & Jain, 2014;Yang, 2015;Zhu & Jog, 2012). Though, there were a few studies claimed that bidding shareholder loss following CBMA announcement (Aybar & Ficici, 2009;Bris & Cabolis, 2008;Cakici et al, 1996;Corhay & Rad, 2000;Ferreira et al, 2010;Jory & Ngo, 2011;Mangold & Lippok, 2008).…”
Section: Market Returnmentioning
confidence: 99%